ANALYSIS OF THE DESIGN AND DEVELOPMENT OF A WEB-BASED CLOTHING SALES APPLICATION FOR LILYS GALLERY - Ken Grinaldy Longdong; Ery Dewayanti (Fakultas Teknologi Informasi Universitas Tarumanagara, 2025)
Lilys Gallery is an online shop that specializes in fashion goods, but currently doesn't have a dedicated website. This limitation affects its market reach and branding efforts. To boost sales and enhance branding for the customers in Jayapura Papua, creating a website is essential. This research focuses on analyzing the design of “developing a web-based clothing sales application for Lilys Gallery”. Using the SDLC waterfall methodology, which includes phases of requirement analysis, system design, implementation, testing, deployment, and maintenance. The website is built using HTML, JavaScript, and PHP, and its structure is designed using UML diagrams, including such as use case diagrams, class diagrams and entity relationship diagrams with the logical database design. The research dives into the process and design of the website, emphasizing usability, user experience, and functionality. The results indicate that a well-crafted website can significantly increase sales, broaden market reach, and strengthen the brand presence of Lilys Gallery in the competitive online fashion market. Furthermore, the study underscores the importance of an integrated online platform for managing inventory, processing sales, and engaging with customers effectively, ensuring a seamless shopping experience and higher customer satisfaction.